21st Century Influence of Southeast Asian Chinese on Regional Politics - Aorigele (International Journal of Social Sciences and Public Administration, 2024)
Amid the increasingly prominent issues surrounding global migration, the successful integration of Chinese diaspora communities within Southeast Asian countries and their impact on the domestic and foreign policies of these nations have emerged as critical topics of academic inquiry. This paper provides a comprehensive analysis of the political and economic engagement of the Chinese diaspora in their host countries, exploring how they navigate and adapt to the evolving policy landscape and socio-political dynamics of Southeast Asia in the 21st century. Through active participation in political processes, these communities have adopted various strategies to legally and effectively safeguard their interests within the complex political frameworks of their host countries. Utilizing a historical analytical approach, this study examines the long-term transformation of Chinese diaspora communities, offering insights into their present roles and functions in relation to political strategy and projecting potential future trends. The findings suggest that the political involvement of the Chinese diaspora in Southeast Asia is on the rise, marked by a significant shift from a focus as primarily an “economic group” to an influential “political group.” This transformation underscores the expanding role of the Chinese diaspora in Southeast Asian societies, with potentially profound and enduring implications for the region’s political landscape and inter-regional relations.